Anmeldelser - Balling, Jakob; Christiansen, Erik; Geertz, Rita; Gregersen, Niels Henrik; Lemche, Niels Peter; Pedersen, Else Marie Wiberg; Pedersen, Nils Arne; Tybjerg, Tove; Warburg, Margit (Religionsvidenskabeligt Tidsskrift, 1991)
n/a